Prioritizing Pituitary Adenoma Care in Pakistan: Analysis from an Epidemiological Study - Mashal Murad Shah; Mohammad Hamza Bajwa; Muhammad Usman Khalid; Rashid Jooma; Saad bin Anis; Altaf Ali Laghari; Muhammad Faraz Raghib; Naveed Zaman Akhunzada; Sameen Siddiqi; Syed Ather Enam (Journal of the Pakistan Medical Association, 2022)
Objective: To identify symptoms and risk factors and promptly diagnose, treat, and manage pituitary adenomas. Prioritizing care for pituitary adenomas will reduce the prolonged disability. Methods: Patients with a histopathological diagnosis of a pituitary adenoma that presented at 32 tertiary care neurosurgical centres were included. The information recorded included demographics, treatment methods, adjuvant chemoradiotherapy and loss to follow-up. Data on tumour size, functionality, and laterality were collected. Results: Of the 32 hospitals surveyed, 24 operated on pituitary adenomas, and treated 277 patients. The mean age at diagnosis was 39.8 ± 13 years, with a majority of males (63.5%) being diagnosed than females. Paediatric cases constituted only 4.7% of the total pituitary adenomas operated upon. Gross total resection was reported for 155 (56%) of all pituitary adenoma patients. Majority of the patients affected by pituitary adenomas (80.1%) were from the working class. Conclusion: Highlighting care for non-malignant brain tumours is important for Pakistan’s health system. Evidence pertaining to gender and age disparities indicates that males in the younger age groups are predominantly affected, which takes a large socio-economic toll on patients and their households. This study also highlights the need to incorporate digital health technologies for postoperative follow-up and adjuvant treatment. Keywords: Pituitary Neoplasms, Chemoradiotherapy, Healthcare, Socioeconomic Factors, Demography. Continue...